Validity and Reliability Analysis of Bullying Comprehension Test Instrument Development - Faridatus Syahroch, Ivon; Khotimah , Khusnul (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: To ensure that the instrument measuring elementary students' bullying comprehension is valid and reliable, so that the data obtained is accurate and trustworthy. This study also aims to validate its content to ensure all measured aspects match the intended construct and are suitable for field trials and further research. Methodology: A descriptive quantitative method is used in this study, with 28 grade 5 students from Sawojajar 1 Elementary School as research subjects and expert validation. The object of this research is a 50-item bullying understanding test instrument. The data obtained were analysed using SPSS with the Pearson Bivariate Correlation technique and Cronbach's Alpha analysis. Main Findings: This study demonstrates that the developed instrument meets validity and reliability standards, making it effective for measurement purposes. Content validity was verified through expert validation, resulting in a score of 97.5%, which falls into the category of highly valid. The validity of the 50 question items resulted in 28 valid items. The valid items produced a Cronbach's alpha value of 0,919, confirming the reliability and consistency of the instrument. Novelty/Originality of this study: Developing valid and reliable instruments to measure elementary school students' understanding of bullying, which were previously unavailable in a standardized and empirically tested form. Through validation and reliability testing, this study ensures that the instrument can be used effectively for measurement purposes, thereby improving the accuracy and consistency of the data obtained.